Islam and the Blackamerican : looking toward the third resurrection - Jackson, Sherman A. (Oxford University Press, 2005)
Why has Islam spread among Blackamericans but not among white Americans or Hispanics? The assumption has been that there is an African connection, but the historical record does not bear this out. In this book, the author offers a trenchant examination of the career of Islam among Blackamericans.